2022
DOI: 10.1039/d1cp05192j
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the solid state luminescence and piezochromic properties in polymorphs of an anthracene derivative

Abstract: Luminescent molecular crystals have gained significant research interest for optoelectronic applications. However, fully understanding their structural and electronic relationships in the condensed phase and under external stimuli remains a significant...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 77 publications
(104 reference statements)
0
7
0
Order By: Relevance
“…There have been 8 polymorphs of 5-methyl-2-[(2-nitrophenyl)­amino]-3-thiophenecarbonitrile, commonly known as ROY, and their electronic band gaps have been calculated to be 1.12–1.84 eV depending on crystal structures . In another case, band gaps of two polymorphs of 9,10-bis­((E)-2-(pyridin-4-yl)­vinyl)­anthracene (BP4VA) have been reported to be 1.58 and 1.26 eV in the literature . Using the trained model, medium CrystGraph of ROY afforded 0.40 eV MAE, and BP4PV resulted in 0.52 eV MAE (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been 8 polymorphs of 5-methyl-2-[(2-nitrophenyl)­amino]-3-thiophenecarbonitrile, commonly known as ROY, and their electronic band gaps have been calculated to be 1.12–1.84 eV depending on crystal structures . In another case, band gaps of two polymorphs of 9,10-bis­((E)-2-(pyridin-4-yl)­vinyl)­anthracene (BP4VA) have been reported to be 1.58 and 1.26 eV in the literature . Using the trained model, medium CrystGraph of ROY afforded 0.40 eV MAE, and BP4PV resulted in 0.52 eV MAE (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“… 30 In another case, band gaps of two polymorphs of 9,10-bis((E)-2-(pyridin-4-yl)vinyl)anthracene (BP4VA) have been reported to be 1.58 and 1.26 eV in the literature. 31 Using the trained model, medium CrystGraph of ROY afforded 0.40 eV MAE, and BP4PV resulted in 0.52 eV MAE ( Figure 6 ). The result, a smaller error of ROY than BP4VA, may be attributed to the difference in a polymorphic manner.…”
Section: Resultsmentioning
confidence: 99%
“…239 DFT using PBCs or QM/MM approaches are often used to identify the intermolecular interactions responsible for this effect, for example, π À π and CH À π interactions (Figure 7). [240][241][242][243][244] In a mixed experimental/ computational study, it was found that intermolecular interactions may even become so strong under pressure that an electron can be transferred, which has tremendous influence on the piezochromic behavior of the system. 245 At the molecular level, minute changes in dihedral angles, for example, those modulating the overlap of neighboring π systems, or the planarity of individual π systems play an important role in piezochromic behavior.…”
Section: Spectroscopic Properties: Piezochromism and Vibrational Spectramentioning
confidence: 99%
“…DFT using PBCs or QM/MM approaches are often used to identify the intermolecular interactions responsible for this effect, for example, ππ$$ \pi -\pi $$ and CHπ$$ \mathrm{CH}-\pi $$ interactions (Figure 7). 240–244 In a mixed experimental/computational study, it was found that intermolecular interactions may even become so strong under pressure that an electron can be transferred, which has tremendous influence on the piezochromic behavior of the system 245 …”
Section: Applicationsmentioning
confidence: 99%
“…The mechanical deformation of a molecular material leads to structural changes at the atomic level in the form of modifications in the geometries of its constituent molecules or, in case a crystal is considered, its crystal lattice parameters. These mechanically induced geometric changes at the atomic level can give rise to spectroscopic signals, which can be exploited in the design of mechano-1,2 and piezochromic [3][4][5] materials. Of particular interest in this regard are mechanophores, i.e., small molecular units that respond to mechanical deformation by profound structural changes such as bond rupture.…”
Section: Introductionmentioning
confidence: 99%